The Role of Personality Factors Influencing Consumer Video Game Engagement in Young Adults: A Study on Generic Games - Abbasi, A.Z. (Institute of Electrical and Electronics Engineers Inc., 2021)
This study aims to investigate the impact of personality dimensions on consumer videogame engagement. We distributed the study questionnaire to gamers aged 16-19 years and managed to get three-hundred-and-eighty valid respondents who provided data in the form of a self-report using HEXACO-100 items and consumer videogame engagement constructs. WarpPLS 7.0 version was employed and the impact of personality dimensions on consumer videogame engagement was assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Our findings indicate that personality traits such as consciousness and extraversion impact consumer videogame engagement, whereas agreeableness, emotionality, openness-to-experience, and honesty-humility do not. Our study explores the utility of the HEXACO-100 item to assess the personality factors that can predict consumer videogame engagement. The article discusses the results and offers the practical and theoretical implications of our findings. Â© 2013 IEEE.